Promotional activities in increasing sales by Ikhlas Consultant & Services, Skudai / Fifizilla Ahmad Sukaimi - Ahmad Sukaimi, Fifizilla (Faculty of Business and Management, 2011)
Ikhlas Consultant & Services (ICS) is one of financial consultant company which promotes Takaful Ikhlas products. The issue statement to be discussed is promotion activities done by the company to increase sales as to achieve the higher sales targeted. The purpose of this study is to suggesting company with the suit of promotion in order to make sure that company practices are fully effective. Data being collected by conducting interview and do observation. The company needs to improve some of promotion activities practices in order to sustain in the market now is tough. This is because of the number of competitors who are already in the market and new in the market are increases. Besides, company may apply another two promotional tools as it did not apply yet which are sales promotion and event and experience.